2013
DOI: 10.4062/biomolther.2013.072
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Transforming Growth Factor-β Signaling in Cancer Therapy

Abstract: TGF-β pathway is being extensively evaluated as a potential therapeutic target. The transforming growth factor-β (TGF-β) signaling pathway has the dual role in both tumor suppression and tumor promotion. To design cancer therapeutics successfully, it is important to understand TGF-β related functional contexts. This review discusses the molecular mechanism of the TGF-β pathway and describes the different ways of tumor suppression and promotion by TGF-β. In the last part of the review, the data on targeting TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 85 publications
0
73
0
1
Order By: Relevance
“…In this work, we show that blockade of the TbR1/PDGFR axis or downstream PI3K-AKT pathway impaired invadosome formation, a process previously linked to cartilage damage (5,6). Various small-molecule inhibitors of TGF-b are being evaluated in preclinical and clinical trials (96). Furthermore, several inhibitors that target PI3Ks are currently being tested in clinical trials for treatment of human cancers (97,98) and are under consideration for the treatment of RA (99).…”
Section: Discussionmentioning
confidence: 87%
“…In this work, we show that blockade of the TbR1/PDGFR axis or downstream PI3K-AKT pathway impaired invadosome formation, a process previously linked to cartilage damage (5,6). Various small-molecule inhibitors of TGF-b are being evaluated in preclinical and clinical trials (96). Furthermore, several inhibitors that target PI3Ks are currently being tested in clinical trials for treatment of human cancers (97,98) and are under consideration for the treatment of RA (99).…”
Section: Discussionmentioning
confidence: 87%
“…However, several reports have indicated that puerarin suppressed TGF-β expression in diabetic rats (She et al, 2014), mice with myocardial fibrosis (Chen et al, 2012b), and rats with hepatic fibrosis . The TGF-β pathway has a dual role in both tumor suppression and tumor promotion (Sheen et al, 2013). Zarzynska reported that in the early stages of breast cancer, TGF-β inhibited epithelial cell cycle progression and promoted apoptosis to suppress tumorigenesis (Zarzynska, 2014).…”
Section: Journal Of Agricultural Sciencementioning
confidence: 99%
“…3,4 A wide variety of signaling pathways and transcription factors have been found to be deregulated during the multistep processes of tumorigenesis of colorectal cancer, such as Wnt/b-catenin, Hedgehog, TGFb/Smad, Snail, and Notch signaling pathways. [5][6][7] It is, thus, widely accepted that colorectal cancer results from the accumulation of the alteration of multiple, not a single, signaling pathway. However, the coordination of these deregulated cancer signal pathways in the development, progression and maintenance of colorectal cancer is largely unknown.…”
Section: Introductionmentioning
confidence: 99%